2012
DOI: 10.1152/ajpgi.00345.2012
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus acidophilus upregulates intestinal NHE3 expression and function

Abstract: A major mechanism of electroneutral NaCl absorption in the human ileum and colon involves coupling of Na(+)/H(+) and Cl(-)/HCO(3)(-) exchangers. Disturbances in these mechanisms have been implicated in diarrheal conditions. Probiotics such as Lactobacillus have been indicated to be beneficial in the management of gastrointestinal disorders, including diarrhea. However, the molecular mechanisms underlying antidiarrheal effects of probiotics have not been fully understood. We have previously demonstrated Lactoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 32 publications
2
28
0
1
Order By: Relevance
“…Also, enteropathogenic bacteria inhibit (86), whereas commensal Lactobacillus acidophilus upregulates intestinal NHE3 expression and function (87). Inhibition of NHE3 expression and activity has been described in several experimental models of colitis, including IL-2 −/− mice (88), and in DSS- and TNBS-induced colitis (89).…”
Section: Epithelial Electrolyte Absorption: Ibd-associated Diarrhea Amentioning
confidence: 99%
“…Also, enteropathogenic bacteria inhibit (86), whereas commensal Lactobacillus acidophilus upregulates intestinal NHE3 expression and function (87). Inhibition of NHE3 expression and activity has been described in several experimental models of colitis, including IL-2 −/− mice (88), and in DSS- and TNBS-induced colitis (89).…”
Section: Epithelial Electrolyte Absorption: Ibd-associated Diarrhea Amentioning
confidence: 99%
“…This intestinal transport mechanism, mediated primarily by NHE3, plays a critical role in the intestinal sodium and water absorption, regulation of intracellular pH, as well as the acidity of the apical microenvironment. NHE3 expression and/or activity is inhibited by proinflammatory cytokines (3,19) and enteropathogenic bacteria (9), whereas commensal Lactobacillus acidophilus upregulates intestinal NHE3 expression and function (24). Inhibition of NHE3 expression and/or activity has been described in several experimental models of colitis, including IL-2 Ϫ/Ϫ mice (3), IL-10 Ϫ/Ϫ mice (17), and in dextran sodium sulfate (DSS)-and trinitrobenzene sulfonic acid-induced colitis (27).…”
mentioning
confidence: 99%
“…Our results demonstrated that Lactobacillus acidophilus , an important gut commensal, counteracted PAF induction of Bcl10-dependent NF-κB activation and IL-8 production in intestinal epithelial NCM460 and Caco-2 cells. Earlier we have shown that this specific strain of L. acidophilus, and more importantly its conditioned culture supernatant, exhibited pro-absorptive effects via distinct mechanisms to stimulate intestinal absorption of NaCl, thereby defining its novel therapeutic potential to ameliorate diarrhea associated with IBD [43], [44]. Interestingly, our current studies also showed that heat-killed LA failed to attenuate PAF-induced increase in nuclear p65 and importantly, bacteria-free CS of LA was as effective as live LA in attenuating the PAF effects on nuclear p65, indicating that LA effects on PAF-induced NF-κB activation are mediated by secreted soluble factor(s) in the CS.…”
Section: Discussionmentioning
confidence: 99%